2015
DOI: 10.1111/jvim.12544
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Severity Score System in Dogs with Degenerative Mitral Valve Disease

Abstract: Background: Several risk factors already have been determined for dogs with degenerative mitral valve disease (DMVD). Risk factors often have been considered in isolation and have not always taken into account additional information provided by the history and physical examination (PE).Hypothesis/Objectives: Data obtained from history and PE of dogs with DMVD provide prognostic information and can be used for risk stratification.Animals: Client-owned dogs (n = 244) with DMVD recruited from first opinion practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 33 publications
9
41
1
5
Order By: Relevance
“…Therefore, the explanation that cough is caused by cardiomegaly and concomitant airway abnormalities, rather than pulmonary oedema, appeared to be supported also by these results (Lopez‐Alvarez et al . ).…”
Section: What Is the Current Evidence On Cardiac Cough?mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the explanation that cough is caused by cardiomegaly and concomitant airway abnormalities, rather than pulmonary oedema, appeared to be supported also by these results (Lopez‐Alvarez et al . ).…”
Section: What Is the Current Evidence On Cardiac Cough?mentioning
confidence: 97%
“…Lopez‐Alvarez et al . () reported that coughing appeared independently associated with higher hazard of cardiac‐related death. However, in this study, dogs developed cough during the clinical progress of their disease at a much earlier stage than they developed overt signs of CHF.…”
Section: What Is the Current Evidence On Cardiac Cough?mentioning
confidence: 99%
“…Therefore, the study of prognostic indicators of mortality in this population of animals is of primary importance. Several studies have focused on evaluating clinical and echocardiographic variables that may predict cardiac mortality in dogs with MMVD . Because echocardiography is the most commonly used diagnostic test in assessing dogs with cardiac disease, it is also the most studied technique for stratification of dogs with cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on evaluating clinical and echocardiographic variables that may predict cardiac mortality in dogs with MMVD. [4][5][6][7] Because echocardiography is the most commonly used diagnostic test in assessing dogs with cardiac disease, it is also the most studied technique for stratification of dogs with cardiac disease. Different Doppler variables, two-dimensional (2D) echocardiographic indicators of mitral valve (MV) pathology, and degree of left atrial (LA) dilatation are strong predictors of cardiac-related death in dogs with MMVD.…”
Section: Introductionmentioning
confidence: 99%
“…The lengthening of MST and a good quality of life (QoL) are significant aspects of the therapeutic strategy, and both are very important for the owners. The achievement of a longer MST in our study compared to the literature might be explained by the good compliance of the owners over time, even given the complex protocols [38]. Prospective studies are needed to investigate the compliance effects of owners and the influence of more standardized therapeutic protocols on the QoL and the survival of dogs with DMVD.…”
Section: Discussionmentioning
confidence: 79%